Parental Involvement Effects in Promoting Students’ Self-Efficacy and Learner Autonomy of The English Language - Daffa Putra Amrullah Sigit; Syafi'ul Anam (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research investigated the effects of parental involvement in promoting EFL students’ self-efficacy and learner autonomy. A total number of 204 students at the high school level in Surabaya with each representing parent of each student participated in this study. Students participating in this research filled out two close-ended questionnaires measuring their self-efficacy, incorporating a scale of 1 to 100 with the increments of 10, and a 5-point Likert scale for their learner autonomy levels. One representative parent for each student also completed a close-ended questionnaire with 5-point Likert scale to measure their parental involvement towards students’ home-based English learning activities. Using quantitative methods, both students’ self-efficacy and learner autonomy levels were descriptively analyzed, revealing that there were more students in the low levels of both variables rather than in the moderate and high levels. Moreover, comparisons of those levels were made among varying parental involvement levels as the independent variable where students’ self-efficacy and learner autonomy were regarded as the dependent variable. Post hoc comparisons revealed that parental involvement significantly affected both students’ self-efficacy and learner autonomy with a great magnitude. The mean differences further showed that the impact was significant between all levels of low and moderate, moderate and high, as well as low and high parental involvement. This study therefore provides support to Bandura’s triadic reciprocal determinism in the context of promoting EFL students’ self-efficacy and learner autonomy through the scope of the extents to which parents are involved to the students’ English language learning at home.